1970
DOI: 10.1079/wps19700033
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Egg Shell Quality—A Review

Abstract: Japan ACTORS influencing egg shell quality have been investigated by F numerous researchers. This article is presented in an attempt to share a comprehensive, but not all-inclusive, review of factors, except genetic, influencing egg shell quality. The review was done in conjunction with an investigation concerning a cracked egg problem in caged turkey breeder hens (1, 2).A review of the various techniques and devices which have been used to evaluate shell quality has not been included because of recent publish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
18
0
1

Year Published

1974
1974
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(23 citation statements)
references
References 238 publications
4
18
0
1
Order By: Relevance
“…Sodium bicarbonate has been commonly used but in terms of shell strength the results have not been consistent (Wolford and Tanaka, 1970). Cohen and Hurwitz (1974), however, reported that there was no decrease in blood pH during shell formation in hens fed semi-purified diets in which the ratio of sodium plus potassium to chloride ((Na + K)/Cl) was greater than 1.5.…”
Section: Introductionmentioning
confidence: 97%
“…Sodium bicarbonate has been commonly used but in terms of shell strength the results have not been consistent (Wolford and Tanaka, 1970). Cohen and Hurwitz (1974), however, reported that there was no decrease in blood pH during shell formation in hens fed semi-purified diets in which the ratio of sodium plus potassium to chloride ((Na + K)/Cl) was greater than 1.5.…”
Section: Introductionmentioning
confidence: 97%
“…Irritated or frightened hens have been shown to lay eggs with thinner shells (Wolford and Tanaka, 1970). The insertion of electrodes in the brain (Wolford and Tanaka, 1970), the injection of an orthophosphate solution into the uterus (Ogasawara ££«/., 1975), and parathyroidectomy (Polin and Sturkie, 1957) resulted in the production of SS or SL eggs.…”
Section: Introductionmentioning
confidence: 99%
“…F ACTORS influencing egg shell quality have been investigated by numerous researchers, especially since the onset of automated egg handling, and have recently been reviewed by Wolford and Tanaka (1970). Many techniques and devices have been used to measure egg shell quality and their relationship to other factors have been reviewed as well (Tyler, 1961;Hunton, 1969;Hammerle, 1969).…”
Section: Introductionmentioning
confidence: 99%